The accounts receivable management in commercial enterprises of the installation and heating industry = Gospodarowanie należnościami w przedsiębiorstwach handlowych branży instalacyjno-grzewczej - Roszkowska-Hołysz, Dorota (Zielona Góra: Faculty of Economics and Management Press)
The article presents the issues of managing current assets in trade enterprises on the market of sanitary and heating devices and installations. It is a capital intensive activity and the current assets being receivables are characterized by a high risk level. Distributors finance executing companies, which commonly use trade credit.
Keywords: majątek obrotowy; kredyt kupiecki; rynek instalacji sanitarno-grzewczych; current assets; merchant credit; trade credit; market of sanitary and heating installations